Cerita dari Timur Genre dan tema dalam Sastra Hindia-Belanda dari masa VOC - Suprihatin, Christina T. (Wacana, Journal of the Humanities of Indonesia, 2008)
This article attempts to give a brief picture about the genre and themes in the Dutch-Indies Literature from the VOC period. During the VOC-period, more than six months was needed to embark on a journey by sea from the Netherlands to Batavia. Undertaking this journey meant encountering many obstacles which occurred through the work of man as well as nature. In addition, a successful landing on the shores of the East did not always ensure a friendly reception. Due to these obstacles which they encountered, only a small number of those who had set sail from Europe were able to return home safely. Most of those who managed to survive this long and dangerous journey to the land of spices, finally chose to stay and start a new life in the East. Some of these men, in an effort to establish their new life, were able to make contact and build relationships with the local women. This paved the way for the emergence of the Mestis culture, in which we find the elements of East and West.